103 New zealand hospital stroke service provision: a national survey. (29th July 2019) - Thompson, Stephanie; Douwes, Jeroen; Barber, Alan; Cadilhac, Dominique; McNaughton, Harry; Gommans, John; Fink, John; Davis, Alan; Feigin, Valery; Ranta, Anna
Abstract : Introduction: The REGIONS Care study assesses stroke care throughout New Zealand. It includes a national audit and here we present organisational survey results assessing current availability of interventions and management approaches in each hospital. Methods: All 20 District Health Boards were invited to complete a survey about patients managed per annum, care setting, and service provision. Results were grouped into rural and urban groups to assess for geographic differences. Results: All NZ hospitals managing stroke patients completed the survey. Results found that of these hospitals 92% have an acute stroke unit, 85% have a TIA pathway, but only 58% offer rapid access specialist TIA services. 100% offer thrombolysis, 92% use pre-hospital notification and rapid ED triage system, and 73% an in-hospital 'code stroke' alert. 50% have access to thrombectomy. Only 32% offer a dedicated inpatient stroke rehabilitation unit. While 92% provide community rehabilitation, only 11% offer early supported discharge programmes. 87% routinely provide stroke patient education, but only 54% provide individualised stroke care plans at discharge. Only 28% have access to a psychologist. In-hospital stroke alerts (p=0.014), access to thrombectomy (p=0.016), access to stroke unit care (p=0.027), and routine referral to stroke foundation (p=0.049) were more common in urban areas. Conclusion: The results of this organisational survey indicates that stroke care provision has improved since the last audit in 2009, but important gaps remain. These results will help services focus on specific areas for improvement, some of which such as pre-hospital alerts should be relatively easy to address.